CERITA RAKYAT INDONESIA SEBAGAI MATERI PEMBELAJARAN BIPA: MENGUSUNG MASA LALU UNTUK PEMBELAJARAN BIPA MASA DEPAN - Kusmiatun, Ari (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2018)
Abstract(Title: Indonesian Folklore as a BIPA Learning Material: Embracing the Past for BIPA Learning in The Future). Learning material has always been an interesting and crucial topic in the field of BIPA. This qualitative research collected the data from observation, document, and interview. The results show that Indonesian folklore has been included in some of BIPA materials, but it has not been used optimally and proportionally as integrative learning materials. Folklore carries local wisdom of local society and can be used as integrative language learning materials, connecting language and culture. Indonesian folklore (written, oral, and/or multimodal texts) can be integrated in BIPA to discover a deeper meaning behind the folklore in accordance with the context of the community. The understanding of Indonesian folklore will help students understand Indonesian more authentically and contextually. Folklore is about the past, but it can be used as a bridge for BIPA learning in the future. Teachers need to create fun activities when integrating folklore in the classroom.Keywords: folklore, BIPA learning materials, integrative BIPA learning